Sustaining Islamic Education Through Family Governance: Evidence from a Three-Generation Tuition-Free Madrasah - Suheri Suheri (JUMPA : Jurnal Manajemen Pendidikan, 2025)
The survival of private Islamic schools that operate without tuition income remains poorly understood in educational management research, which tends to explain sustainability through financial capacity and administrative efficiency. This study asks how family governance sustains Madrasah Al Islah, a tuition-free madrasah that has run across three generations in Bondowoso, Indonesia. A qualitative single-case design was used, drawing on semi-structured interviews, participant observation, and document analysis involving the headmaster, two teachers from the founder's family, and two parents. The data were analyzed through the interactive model of Miles, Huberman, and Saldaña, and trustworthiness rested on triangulation together with the criteria of Lincoln and Guba. The findings show that sustainability grows from the interaction of five elements: intergenerational leadership, family commitment, Islamic ethical values, tuition-free educational management, and community trust. Working together, these elements form a governance ecosystem that preserves the institution's identity, reinforces its legitimacy, and keeps its educational mission alive despite the absence of tuition revenue. From this pattern the study proposes the Family Governance for Sustainable Islamic Education (FGSIE) framework, which treats family governance as a strategic mechanism binding leadership continuity, ethical stewardship, and community engagement. The study implies that policymakers and leaders of faith-based schools can strengthen institutional resilience in resource-scarce settings by nurturing shared values across generations and cultivating community trust rather than relying on tuition as the primary guarantee of continuity.